Discussion - Of Mr. Gayley's Paper on the Application of Dry-Air Blast to the Manufacture of Iron (see p. 746) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
Discussions of the paper of Mr. Gayley read by title at the Lake Superior hieeting, but first presented at the New York meeting of the Iron and Steel Institute, October, 1904 (see p. 746). With the exception of Mr. Pourcel's discussion (p. 1038), these papers are here published under a mutual agreement between the Councils of the two Institutes, and will also be found, with others, in the Journal of the Iron and Steel In-slitute for the pear 1904, Mr. E. Windsor Richards, Past-President,' said that in 1799 Mr. Dawson, of Low Moor, read a paper before a scientific society in York pointing out the great diff'erence in the moisture of the air going into the blast-furnace in the hot months of the year and in the winter months. A cold blast-furnace was a very sensitive instrument, and showed this very clearly, for in June, July and August the furnace did not drive so well; it did not make the quality of iron and required more fuel; so that Mr. Gayley was on the right road to effect an enormous improvement in this direction. He considered that Mr. Gayley was on the way to great success, and hoped that the apparatus would not be a very expensive one. He supposed it mas too early for Mr. Gayley to let them know what the saviug was